Gangguan Ekosistem Laut sebagai Dampak Keberadaan PLTU Teluk Sepang Bengkulu: Sebuah Telaah Pustaka - Sefri Oktaviani; Sri H. Siregar; Rizki Fauzi; Reflis, Reflis; Satria P. Utama (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
However, the people who work as fishermen feel disadvantaged because they cannot find fish and other marine animals as a livelihood due to the damage to the marine ecosystem caused by PLTU waste. However, people who work as fishermen feel lost because they cannot find fish and other marine animals as a livelihood due to damage to the marine ecosystem caused by PLTU waste. This literature review aims to provide information to the company, government, and community regarding the impacts caused by the existence of the Teluk Sepang PLTU and recommendations for solutions that can be applied to minimise the impact of pollution. The results of the review show that the discharge of wastewater from the Teluk Sepang PLTU has the potential to cause the parameters of temperature, salinity, pH, and turbidity of seawater to be incompatible with quality standards. Damage to marine ecosystems can also be caused by coal spills from barges. This causes all marine ecosystems to be disrupted, ultimately causing the community to experience economic losses. Three strategies can be recommended in an effort to control marine pollution due to the presence of the Teluk Sepang PLTU, namely increasing the efficiency of coal fuel use, managing liquid waste effectively, and increasing water use efficiency.